VD_FINDINFO AP / 2010 / 267 vom 8. September 2010 - VD Tribunal cantonal (2010)
DÉPENS, APPEL EN CAUSE | 160 al. 1 CPC, 162 CPC, 83 al. 1 let. a CPC, 86 CPC, 88 al. 1 CPC, 91 let. a CPC, 94 CPC, 2 let. a ch. 2 TAg